The Antibacterial Properties of Psidium guajava Leaf Extract as a Wound Healing Agent of Laboratory Animals: a Review - Carolino, Maria Victoria; Purnamasari, Listya; dela Cruz, Joseph F. (Universitas Brawijaya, 2022)
The importance of Psidium guajava has long been reported in ethnomedicine. Traditional medicine is practiced all over the world and is significant most especially in indigenous groups due to the poor accessibility to conventional medicine in the area. Furthermore, this type of medical approach is costly, and antibiotic resistance has been a serious issue ever since. The scientific community, therefore, studies good alternatives such as plant-derived extracts to treat various illnesses and diseases, which are known to be less expensive in terms of preparation, have fewer side effects, and be the less potential promoters of antibiotic resistance. One of the most encountered conditions in veterinary medicine is a wound. The review collated and presented studies, research, experiments, and other published materials that proved the antibacterial properties of P. guajava leaf extract, which causes the wound healing activities of the extract. P. guajava leaf extract is an effective alternative to commercially available drugs in treating wounds of laboratory animals and could potentially be effective in the larger scope of animals in the future.